Citizen security as a human right. The duty of prevention - Figueroa Gutarra, Edwin (2024)
The notion of citizen security leads us to the idea of this as true human right, as there is material insufficiency in the idea of a simple demand for the security of the population. At the same time, of this correlation between citizen security and human rights it appears a strong premise: the duty of prevention that assists it does not only to the State, but to society as a whole for the construction of solid public policies regarding citizen security. It is so we forged the concept of militant citizenship.